Affiliate and Content Marketing Impact Purchase Decision on E-Commerce Moderated by COD - Wachjuni; Oktaviani, Winda; Mahsyar, Januar Habibi (Forum Kerjasama Pendidikan Tinggi, 2025)
Digital era, e-commerce leverages various online marketing strategies to reach consumers. Popular methods include affiliate marketing and social media content. However, a major challenge is the low level of consumer trust in online purchases. To address this, the Cash on Delivery (COD) payment method has emerged as a solution, allowing consumers to inspect goods before payment. This study aims to explore the moderating effect of COD on the relationship between affiliate marketing, social media content, and consumer purchase decisions in e-commerce. Specifically, it analysis the impact of affiliate marketing and social media content on purchase decisions and identifies the role of COD as a moderating variable. The study investigates whether the availability of COD can strengthen or weaken the influence of online marketing on consumer purchase decisions. Using a quantitative approach, data is collected through an online survey targeting e-commerce consumers in Indonesia. The data is analysed using the Moderated Regression Analysis (MRA) method to test the research hypotheses and identify the moderating effects of COD with 240 respondents. The findings suggest that while both affiliate marketing and social media content independently influence online shopping decisions, the presence of Cash on Delivery (COD) as a moderating variable strengthens the effect of affiliate marketing more significantly. This indicates that COD enhances consumer trust particularly when purchases are driven by affiliate recommendations, compared to when decisions are influenced by social media content only